Rediscovery of Biswamoyopterus (Mammalia: Rodentia: Sciuridae: Pteromyini) in Asia, with the description of a new species from Lao PDR - Sanamxay, Daosavanh; Douangboubpha, Bounsavane; Bumrungsri, Sara; Xayavong, Sysouphanh; Xayaphet, Vilakhan; Satasook, Chutamas; Bates, Paul J.j. (Zootaxa, 2013)
A new species of the flying squirrel genus Biswamoyopterus is described from Lao PDR. It is based on a single specimen collected from a local food market at Ban Thongnami, Pak Kading District, Bolikhamxai Province. The new taxon shows close affinities to Biswamoyopterus biswasi, which is only known from the holotype collected in 1981, 1250 km from the current locality, in Arunachal Pradesh, Northeast India. However, it differs substantially in pelage colour, most particularly on the ventral surfaces of the body, patagia, tail membrane, and tail. The single specimen was found in an area of central Lao PDR, which is characterised by its extensive limestone karst formations and which is home to other rare endemic rodents, including the Kha-nyou (Laonastes aenigmamus) and the Lao limestone rat (Saxatilomys paulinae).